ARTISTIC FREEDOM AND LEGAL BOUNDARIES: NAVIGATING CENSORSHIP AND EXPRESSION IN INDONESIA’S DEMOCRATIC FRAMEWORK - Wiratraman, Herlambang P. (Faculty of Law, Universitas Diponegoro, 2025)
Art has increasingly become a target for political agendas, often subjected to legal restrictions that limit freedom of expression. This phenomenon is evident in countries like Myanmar, where several laws have been enacted to criminalize speech, surpassing international legal standards. In Indonesia, the rise of authoritarian tendencies has been linked to the weakening of artistic freedom, as reflected in the rising number of cases of artistic repression. This study explores the legal and practical realities of artistic freedom in Indonesia, addressing how the legal system handles attacks on artistic expression and the involvement of state and non-state institutions in strengthening legal protection for artists. It discusses the theoretical framework of artistic freedom, its protection under international human rights law, and Indonesia’s legal context, particularly through laws like the 1945 Constitution and various international agreements such as the ICCPR. The research highlights the challenges of balancing artistic freedom with public morality, security, and order, and critiques the misuse of legal restrictions that often result in excessive censorship. By examining historical and contemporary legal cases, the study proposes an ideal legal framework to ensure robust protection for artistic expression in a democratic society, advocating for a balanced approach between law enforcement and fundamental human rights.